Penyuluhan Internet Sehat Dan Gadget Care Bagi Para Siswa-Siswi SMK Wisata Harapan Massa Depok - Khairudin; Leni Susanti; Zainuddin (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The internet in the era of the 21st century has now become a facility that is easy to get and use. The Internet is the result of the development of technology and information that helps its users access information from various sites easily and quickly. The Internet is a global communication network that connects computers and computer networks around the world. Not only computers, the internet network today can also be enjoyed by smartphone users. By using the internet, users can access any information without being limited in space and time. Smartphone or commonly referred to as a smartphone is an electronic communication tool that allows its users to be able to interact remotely. It is undeniable that the presence of this smartphone is very useful for those who have it, whether it is used to help with office work, business, hobbies, and even worship activities. With smartphones, the world is as if it is boundless in time and space. Everything can be done anytime and anywhere so in the world of education smartphones and the internet can greatly help teachers and their students to continue to carry out distance learning activities during the COVID-19 pandemic. SMK Wisata Harapan Massa Depok is a hospitality school located in the complex area of Depok Indah II Housing Block G No. 15 and Jl. H. Asmawi No. 79 Beji Depok. In teaching and learning activities during the COVID-19 pandemic, educators and students always use internet access and smartphones to provide materials, assignments and completions. The internet and smartphones for students are now an important part that must be owned by both teachers and students. However, in the current developments, teachers and their students not only use the internet and smartphones as learning media, but from both of them they can carry out other activities such as watching videos, playing social media, and can even create content that can be uploaded on YouTube so that many people can see it. The existence of easy internet access today not only has a positive impact on its users but also a negative impact. Similarly, the information obtained is increasingly open, both positive and negative content, various negative impacts caused by the internet such as addiction to playing online games, internet abuse such as gambling, opening porn sites, fraud, cyberbullying, copyright violations such as spreading viruses, making teenagers lazy and rarely get along, ignoring obligations to God Almighty, promiscuity, even committed data theft. The results and outcomes of the activity after the socialization activities were carried out about healthy internet and gadget care were that every student of SMK Harapan Massa Depok, had an understanding and awareness of the importance of healthy internet. Based on the existing problems, the purpose of this socialization is to provide education to the students of SMK Harapan Massa Depok so that they can better use the internet optimally for positive things that support the teaching and learning process. This activity can increase participants' insight into safe and useful sites in the teaching and learning process, as well as increase knowledge about social media functions such as YouTube to find learning videos, upload assignment videos and others.